Seed treatment for management of the green‑belly stink bug in the crop succession of soybean and corn - Chiesa, Ana Carolina Montenegro; Sismeiro, Mariana Nunes dos Santos; Pasini, Amarildo; Roggia, Samuel (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the effect of seed treatment with insecticides on the management of Dichelops melacanthus on the yield of soybean and corn, grown in succession. The study was carried out in a field, in the 2012/2013 (I) and 2013/2014 (II) crop seasons. The evaluated insecticides were: imidacloprid, thiamethoxam, thiodicarb, fipronil, and abamectin. The following were determined: stink bug population density, soybean and corn yield, and corn injury. Population density remained below one stink bug per square meter, in most of the soybean cycle. Population peaks were observed in the first weeks, after corn emergence, and they reached 2.2 (crop season I) and 6.7 (crop season II) stink bugs per square meter. In the soybean crop, the insecticides did not reduce the stink bug population density. In the corn crop, imidacloprid reduced the stink bug density in 23.2% (crop season I) and 38.8% (crop season II), and injury in 61.8% (crop season I) and 26.4% (crop season II). Thiamethoxam reduced the insect population density in 27.8% (crop season II) and injury in 42.7% (crop season I). Seed treatment with insecticides does not provide increase for soybean and corn yields, therefore, their use is not justified in this study's conditions.